A case of the orocraniodigital (Juberg-Hayward) syndrome. Issue 6 (December 1981) - Nevin, N C; Henry, P; Thomas, P T
Abstract : A female with the orocraniodigital (Juberg-Hayward) syndrome is described in whom, in addition to bilateral cleft lip and palate, mild microcephaly, and anomalous thumbs and toes, there was absence of the pituitary fossa and a more widespread skeletal dysplasia.